Quasiparticle band structure study of ternary mixed chalcogenide Bi2Te2S as topological insulator - Alhassan, Shuaibu; Rahman, Md. Mahmudur; Zainuddin, Hishamuddin; Talib, Zainal Abidin; Muhida, Riza; Setiyanto , Henry (National Institute of Research and Development of Materials Physics, 2015)
In this paper, ternary mixed chalcogenide Bi2Te2S has been investigated using first principle within the density functional theory (DFT) calculation as well as many body perturbation theory within the GW quasiparticle approximations. For the DFT calculation, we have used generalize gradient approximations (GGA) as exchange correlation function and found that, Bi2Te2S has a narrow band gap with a band gap of about 0.058eV, while or the GW calculation, we have evaluated both the quarsi bands structure, and absorption spectrum using random phase approximation (RPA). From the results we have observed that the GW corrections to the DFT-Kohn-Sham eigenvalues increase the fundamental band gap to 0.099 eV showing the effect of electron-phonon coupling present in the structure of Bi2Te2S, while, for the absorption spectrum, it exhibits a close value in agreement with the theoretical results of similar compounds reported by (Anjan A. Reijnders, et. al 2014).